Liberty - KUKATHAS, Chandran (Institutional Knowledge at Singapore Management University, 1993)
Such is the rhetorical appeal of the idea of liberty that a variety of political philosophiesclaim to honour it. Republicans and Marxists, no less than libertarians and liberals,maintain that they and they alone are the true defenders of freedom. The literature ofcontemporary political theory is thus replete with rival analyses of the meaning ofliberty, and disputes about its measurement, distribution and institutional requirements. Our aim here is to gain some understanding of the meaning and the conditionsof liberty by working through the thicket of contemporary argument, though we mayhave to rest content with a better knowledge of the terrain.